2020
DOI: 10.1152/advan.00010.2020
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed learning: assessment of students’ abilities and their perspective

Abstract: The introduction of Competency-Based Medical Education Curriculum in India has endorsed many new concepts, like foundation course, self-directed learning (SDL), early clinical exposure, etc. Emphasis is being given to active teaching-learning approaches. One such approach is SDL. SDL is an active learning approach in which the students are responsible for their own learning outcome, with teacher acting as a facilitator of learning. A medical graduate, being a lifelong learner, should inculcate the hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 13 publications
3
47
1
1
Order By: Relevance
“…Another study also showed that the students face difficulty in finding the correct learning resources. 18 Students wanted seminars and other such activities to be conducted as a part of the SDL session to promote active participation of all the students. It has been shown that a change in learning and behaviour in medical students is evident with conduction of such activities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another study also showed that the students face difficulty in finding the correct learning resources. 18 Students wanted seminars and other such activities to be conducted as a part of the SDL session to promote active participation of all the students. It has been shown that a change in learning and behaviour in medical students is evident with conduction of such activities.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of these skills helps students in acquiring self-directed learning skills. 17,18 Although medical students possess most of these skills owing to their vast curriculum and the pace of the course, some of the students have identified lack of time and stress management skills and inter communication skills as some of the areas where they need improvement. 18…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations